Endocrown for extensively damaged teeth from conventional to biomimetic protocols: A review study - Pooya Jannati; Faranak Vakili; Saeid Nokar; Somayeh Zeighami (Tehran University of Medical Sciences, 2023)
Background and Aims: Endocrown is a type of monoblock restoration using the pulp chamber and remaining coronal tooth structure for retention. Advancements in adhesive techniques have breathed fresh spirit into endocrown. Nowadays, there are two approaches for endocrown: conventional approach and  biomimetic approach. This study aimed to review data on the steps and clinical and philosophical points of using these approaches to help dentists' selection and performance. Materials and Methods: The review was conducted by reviewing the articles available in PubMed, Scopus, and Google Scholar databases from 1995 to 2022. The keywords used were; Crown, Endodontically-treated teeth, Light-curing of dental adhesive, Onlay, and Post-Core.   Results: After removing duplicates, titles/abstracts were reviewed. Animal studies, studies without available full text or non-English language studies were excluded from the study. Then, the full texts of the remaining 59 articles were evaluated and 49 articles were eligible for the present study. The articles included clinical trials, in vitro, systematic reviews, and case reports. Conclusion: Endocrown is a successful alternative to crown, especially in molar teeth. Regardless of the conventional or biomimetic approach, this treatment has a more favorable fracture pattern while preserving the remaining tooth tissue as much as possible.